Immobilization of escherichia coli producing β-cyclodextrin glucanotransferase on hollow fiber membrane for β-cyclodextrin production - Nurul Nabila Huda, Baharudin (2023)
β-cyclodextrin is a cyclic oligosaccharide that has been in high demand in various industries due to its numerous applications. It is produced from starch via the enzymatic conversion of β-cyclodextrin glucanotransferase (β-CGTase). While researchers have discovered a method to produce a high concentration of β-CGTase in the medium through excretion by recombinant Escherichia coli (E. coli), cell lysis remains an open problem as hydrostatic pressure builds up in the cytoplasm and periplasmic space of the E. coli. Cell immobilization is a promising solution to reduce cell lysis and enhance enzyme excretion. In the present study, the recombinant E. coli was immobilized using hollow fiber membrane. The production of β-CD was optimized and the reusability of the immobilized cells were evaluated. The effects of substrate concentration, temperature, agitation rate, pH, and time on β-CD production, β-CGTase excretion, and cell lysis by the immobilized cells were determined by using the one factor at a time (OFAT) method. The results revealed that the immobilized cells could produce 11-14-fold more -CD compared to the free cells. The immobilized cells also exhibited a 17-19-fold increase in β-CGTase excretion with a 64-92% reduction of cell lysis compared to free cells. Then, the operating parameters was screened to identify the significant parameters using Full Factorial Design (FFD). It showed that the substrate concentration, temperature and agitation rate were the significant operating parameters and were used for optimization process using Central Composite Design (CCD) under Response Surface Methodology (RSM). Under the optimized conditions (3.9% of starch concentration, 44°C of reaction temperature, and 170 rpm agitation rate), the β-CD production and β-CGTase excretion was 8-fold and 7-fold, respectively higher than before the optimization process. Moreover, the immobilized cells showed 3-fold and 2.5-fold of β-CD production and β-CGTase excretion, respectively with 54% reduction of cell lysis in comparison with the free cells. The immobilized cells successfully retained up to 62% of the initial activity and can be reused for 5 cycles for the production of β-CD. Therefore, the immobilization of E. coli on hollow fiber membrane was suitable for enhancing β-CD production with high excretion of β-CGTase and high cell stability.